Electron impact excitation and ionization cross section of tungsten ions, W44+. (February 2019) - El-Maaref, A.A.; Abou halaka, M.M.; Tammam, Mahmoud; Shaaban, E.R.; Yousef, El Sayed
Highlights: Atomic structure data of tungsten ion, W 44 +, have been computed using different methods. Electron impact excitations and cross sections of W 44 + are performed using R-matrix method. Ionization cross sections by electron impact are calculated and presented in the current work. Abstract: Atomic structure data, electron impact excitations and ionization cross sections of tungsten ions, W 44 +, have been calculated using the multi-configuration Dirac–Fock and R-matrix methods for a set of configurations consists of 3 d 10 4 s 2, 3 d 10 4 s 4 l, and 3 d 10 4 p 4 l . A set of configuration state functions (CSFs) with doubly excitations up to 5 l orbitals have been included within the calculations of energy levels and transition probabilities. As well as, 4-electron excitation to 4 l -levels and 3-electron to 5 l -levels have been involved in the computation process. R-matrix calculations of collision strength and cross section have been executed for the intercombination transitions between 3d 10 4s 2, 3d 10 4s4p, 3d 10 4s4d, and 3d 10 4s4f at different angular momenta using DARC code. Resonance collision strengths have been observed at low energy of incident electron in the range of  ∼ 6 – 40 Ryd, however, the strong lines are limited to 6–25 Ryd. For cross section of various transitions, resonances arising from these transitions are observed at low-electron energies in the range of 6–25 Ryd. To estimate the accuracies of calculated energy levels and transition probabilities, comparisons between experimental observations and theoretical calculations are presented. The convergence between different methods for collision strengths and cross sections are observed. Different calculations of electron impact ionization cross section of the present ion in the collision energy range of 100–1000 Ryd are evaluated.